Kajian Isoterm Dan Kinetika Adsorpsi Logam Arsen Menggunakan Biosorben Kombinasi Kitosan Dan Karbon Aktif Ampas Kopi - Nisa Nurhidayanti; Sandy Nugraha (DPPM Universitas Pelita Bangsa, 2022)
The presence of arsenic metal in water naturally due to its mobility causes the nature of water to become toxic and become a problem in the world. The purpose of this study was to determine the maximum adsorption capacity through the isotherm model and the rate of adsorption kinetics in the use of chitosan and coffee grounds as adsorbent in reducing the concentration of arsenic in industrial wastewater. The research method was carried out using experiments in the laboratory followed by quantitative data analysis to determine the isotherm model and adsorption kinetics. shows that the adsorption isotherm follows the Langmuir isotherm model with a correlation coefficient of 0.9972 with a maximum adsorption capacity of 2.063 mg.g-1 which indicates that chemical adsorption occurs in a mono layer with a homogeneous distribution of adsorption sites with constant adsorption energy and interactions between negligible metal arsenic (adsorbate) molecules. The study of arsenic adsorption kinetics using chitosan-activated carbon coffee grounds followed the Weber-Morris model/intra-particle diffusion with a correlation coefficient of 0.9920 with a diffusion rate of 76.512 g.mg-1.hour-1 which indicates that intra-particle diffusion is a rate step. limiting factor in the overall biosorption process. Keywords: Isotherm, Kinetics, Adsorption, Chitosan, Coffee Grounds